Targeted multispectral filter array design for the optimization of endoscopic cancer detection in the gastrointestinal tract - Taylor-Williams, Michaela; Tao, Ran; Sawyer, Travis W.; Waterhouse, Dale J.; Yoon, Jonghee; Bohndiek, Sarah E. (Journal of Biomedical Optics, 2024)
Significance: Color differences between healthy and diseased tissue in the gastrointestinal (GI) tract are detected visually by clinicians during white light endoscopy; however, the earliest signs of cancer are often just a slightly different shade of pink compared to healthy tissue making it hard to detect. Improving contrast in endoscopy is important for early detection of disease in the GI tract during routine screening and surveillance. Aim: We aim to target alternative colors for imaging to improve contrast using custom multispectral filter arrays (MSFAs) that could be deployed in an endoscopic “chip-on-tip” configuration. Approach: Using an open-source toolbox, Opti-MSFA, we examined the optimal design of MSFAs for early cancer detection in the GI tract. The toolbox was first extended to use additional classification models (k-nearest neighbor, support vector machine, and spectral angle mapper). Using input spectral data from published clinical trials examining the esophagus and colon, we optimized the design of MSFAs with three to nine different bands. Results: We examined the variation of the spectral and spatial classification accuracies as a function of the number of bands. The MSFA configurations tested showed good classification accuracies when compared to the full hyperspectral data available from the clinical spectra used in these studies. Conclusion: The ability to retain good classification accuracies with a reduced number of spectral bands could enable the future deployment of multispectral imaging in an endoscopic chip-on-tip configuration using simplified MSFA hardware. Further studies using an expanded clinical dataset are needed to confirm these findings.
Keywords: Array design; Classification accuracy; Colon cancer; Colonoscopy; Esophageal cancer; Gastrointestinal tract; Healthy tissues; Multi-spectral filter arrays; Multispectral imaging; Optimisations; Diagnostic Imaging; Endoscopy, Gastrointestinal; Esophagus; Humans; Neoplasms; colon cancer; colonoscopy; endoscopy; esophageal cancer; multispectral filter array; multispectral imaging